2020
DOI: 10.1111/acel.13096
|View full text |Cite
|
Sign up to set email alerts
|

Metformin mediates cardioprotection against aging‐induced ischemic necroptosis

Abstract: Necroptosis is crucially involved in severe cardiac pathological conditions. However, whether necroptosis contributes to age-related intolerance to ischemia/reperfusion (I/R) injury remains elusive. In addition, metformin as a potential anti-aging related injury drug, how it interacts with myocardial necroptosis is not yet clear. Male C57BL/6 mice at 3-4-(young) and 22-24 months of age (aged) and RIPK3-deficient (Ripk3 −/− ) mice were used to investigate aging-related I/R injury in vivo. Metformin (125 μg/ kg,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…Results concerning LC3-II are less clear. With regard to C57BL/6J mice: (i) LC3II / GAPDH (Taneike et al, 2010) and LC3II / LC3I (Hua et al, 2011; Ren et al, 2017) declined in hearts from ∼ 26 mo vs. ∼ 4 mo animals; (ii) LC3II / LC3I increased in 18 mo vs. 2 mo mice; (Boyle et al, 2011) and (iii) LC3II / LC3I was not different between ∼ 23 mo and ∼ 4 mo animals (Li et al, 2020; Wu et al, 2016). We observed increased LC3I:GAPDH, LC3II:GAPDH, and p62:GAPDH in older vs. adult mice from two independent cohorts treated identically (Figure 1, Figure 3).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Results concerning LC3-II are less clear. With regard to C57BL/6J mice: (i) LC3II / GAPDH (Taneike et al, 2010) and LC3II / LC3I (Hua et al, 2011; Ren et al, 2017) declined in hearts from ∼ 26 mo vs. ∼ 4 mo animals; (ii) LC3II / LC3I increased in 18 mo vs. 2 mo mice; (Boyle et al, 2011) and (iii) LC3II / LC3I was not different between ∼ 23 mo and ∼ 4 mo animals (Li et al, 2020; Wu et al, 2016). We observed increased LC3I:GAPDH, LC3II:GAPDH, and p62:GAPDH in older vs. adult mice from two independent cohorts treated identically (Figure 1, Figure 3).…”
Section: Discussionmentioning
confidence: 97%
“…A variety of studies indicate p62 accumulates in hearts from aged vs. adult mice (Li et al, 2020; Ren et al, 2017; Wang et al, 2018; Wu et al, 2016; Y. Zhang et al, 2017), and translational relevance of these findings to older humans was recently reported (Li et al, 2020). Results concerning LC3-II are less clear.…”
Section: Discussionmentioning
confidence: 99%
“…Because treatment of diabetic OVE26 mice with metformin activated AMPK and increased autophagy [132], interest sparked with regard to using this compound in the context of cardiac aging. As thought, metformin treatment enhanced contractile function and reduced cardiac fibrosis induced by isoproterenol [133], and protected mice from age-induced ischemic necroptosis [134]. Providing translational relevance, metformin reduced the incidence of age-related cardiovascular disease in type 2 diabetic men [135].…”
Section: Pharmacological and Nutraceutical Interventionsmentioning
confidence: 87%
“…According to these reports, autophagic flux was suppressed as the RIPK1–RIPK3 interaction and necroptosis were induced by the combined treatment with TNFα and a broad-spectrum caspase inhibitor (Ogasawara et al, 2017 ); improving autophagic flux through inhibition of mTORC1 was able to attenuate the necroptosis in an autophagy- and transcription factor EB (TFEB; a master regulator of the ALP)-dependent fashion (Ogasawara et al, 2017 ; Abe et al, 2019 ); and MPT was not important in the execution of necroptosis (Ogasawara et al, 2017 ). More recently, Li C. et al ( 2020 ) reported that aging-associated impairment of autophagy promoted myocardial I-R injury, the protection of metformin against such injury was associated with improving autophagic flux, and the upregulation of p62 resulting from decreased autophagy promoted the interaction of RIPK1 and RIPK3, a key step for the activation of the RIPK1–RIPK3-mediated necroptotic pathway. Given that both necroptosis and autophagic impairment have been shown as mediators in cardiac pathogenesis, it will be extremely important to improve our understanding of the interaction between autophagy and necroptosis in cardiomyocytes as the resultant mechanistic insight is expected to help identify potentially new therapeutic strategies to treat a large subset of heart disease.…”
Section: Interactions Between Macroautophagy and The Ripk1–ripk3–mlkl Pathwaysmentioning
confidence: 99%